1985
DOI: 10.1038/bjc.1985.52
|View full text |Cite
|
Sign up to set email alerts
|

HLA and nasopharyngeal carcinoma in Malays

Abstract: HLA associations were observed in unrelated Malay patients with nasopharyngeal carcinoma (NPC). HLA-B18 was observed in 18/45 (40%) Malay NPC patients compared to 22/167 (13%) Malay normals (P = 0.0001; Pc = 0.0027, RR = 4.4). The frequency of HLA-B17, one of the antigens associated with Chinese NPC, was also increased among Malay NPC (13/45 29%) compared to controls (18/167 11%; P = 0.003, Pc = 0.07 RR = 3.4). Similar to the findings among Chinese NPC, the frequency of B17 was higher in early onset (less than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

1987
1987
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 7 publications
1
21
0
1
Order By: Relevance
“…This may suggest the probable protective role of this allele towards DHF patients in this population. However, others have documented the risk association of HLA-B*18 in Malay patients with nasopharyngeal carcinoma [40]. Furthermore, a probable protective association of HLA-B*18 allele have been reported in breast feeding infants against HIV-1 acquisition [41].…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest the probable protective role of this allele towards DHF patients in this population. However, others have documented the risk association of HLA-B*18 in Malay patients with nasopharyngeal carcinoma [40]. Furthermore, a probable protective association of HLA-B*18 allele have been reported in breast feeding infants against HIV-1 acquisition [41].…”
Section: Discussionmentioning
confidence: 99%
“…among Singapore Chinese. and with a stronger association subsequently reported (OR=3.36, 95%CI=1.36–8.08) among Malaysians[53]. Moreover, a highly significant association was found between HLA-B18 and prevalence of NPC (OR=4.39, 95%CI=1.93–9.84) in the same Malaysian population.…”
Section: Hla Alleles Associated With Npcmentioning
confidence: 75%
“…Moreover, an association was found between HLA-A13 and the survival of patients with NPC that was also associated with a lower risk of developing the disease (OR=0.47, P<0.02). Among a total of twelve studies done subsequently in Guangdong [55], Singapore [20, 22, 29, 31, 34, 52], Taiwan [23, 32], Thailand [33], and Malaysia [53, 56], eight confirmed a significantly negative association between HLA-A11 and prevalence of NPC with an OR ranging from 0.28 to 0.55. The remaining studies consistently indicated a trend toward a low frequency of HLA-A11 in patient with NPC (Fig.…”
Section: Hla Alleles Associated With Npcmentioning
confidence: 99%
“…Another HLA antigen which is associated with NPC is B58, which occurs in both Chinese and Malay patients with NPC [23]. Patients bearing B58 are younger ( < 30 years) than those bearing A2/B46.…”
Section: Hla Haplotypesmentioning
confidence: 99%